2000
DOI: 10.3171/foc.2000.8.4.7
|View full text |Cite
|
Sign up to set email alerts
|

A light and electron microscopic study of ectopic tendon and ligament formation induced by bone morphogenetic protein–13 adenoviral gene therapy

Abstract: Object Bone morphogenetic proteins (BMPs) are involved in the growth and development of many tissues, but it is their role in skeletal development and their unique ability to induce ectopic and orthotopic osteogenesis that has attracted the greatest interest. Expression of the BMP-13 gene has been shown to be predominantly localized to hypertrophic chondrocytes in regions of endochondral bone formation during development, as well as in matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…BMP‐7 encouraged the formation of a denser network of trabecular bone at the reattachment site than was evident in controls. It is also worth noting that BMP‐13 induces neotendon formation with fibrocartilage cell differentiation in skeletal muscle of athymic nude rats (Helm et al. 2001).…”
Section: Enthesis Turnovermentioning
confidence: 99%
“…BMP‐7 encouraged the formation of a denser network of trabecular bone at the reattachment site than was evident in controls. It is also worth noting that BMP‐13 induces neotendon formation with fibrocartilage cell differentiation in skeletal muscle of athymic nude rats (Helm et al. 2001).…”
Section: Enthesis Turnovermentioning
confidence: 99%
“…Several studies have reported neo-tendon/ligament formation and the development of highly organized connective tissue rich in collagen I fibres in response to in vivo ectopic implantation of BMP13 at sites of tendon wounding in rats 61,69,70 and intramuscularly 60,71. Progenitor cell proliferation and differentiation into neo-tendon/neo-ligament was reported within the muscle, the formation of collagenous extracellular matrix, and even development of small bone and cartilage foci within the new tissue 71.…”
Section: Bmp13 Expression and Functionmentioning
confidence: 99%
“…Progenitor cell proliferation and differentiation into neo-tendon/neo-ligament was reported within the muscle, the formation of collagenous extracellular matrix, and even development of small bone and cartilage foci within the new tissue 71.…”
Section: Bmp13 Expression and Functionmentioning
confidence: 99%
“…GDF‐6/BMP‐13 . GDF‐6/BMP‐13 has been shown to stimulate proliferation and collagen production of tendon fibroblasts in vitro (Wong et al , 2005), promote neotendon/neoligament formation after subcutaneous and intramuscular implantation (Helm et al , 2001; Wolfman et al , 1997) and promote tendon repair in vivo (Aspenberg and Forslund, 1999; Forslund and Aspenberg, 2003, 2001; Forslund et al , 2003; Virchenko et al , 2005). The neotendon/neoligament tissue formed in Wolfman et al 's (1997) study resembled matured tendons at both micro‐ and ultrastructural levels and expressed elastin, decorin, collagen type I , sine oculis homeobox homologue 1/2 ( six 1/six 2 ) and aggrecan but not ALP and osteocalcin mRNA, similar to that in developing and matured tendons.…”
Section: Factors Regulating Tenogenic Differentiation Of Stem Cellsmentioning
confidence: 99%